“POLISH ELEMENT” IN THE COLONIZATION STRUCTURES OF LATE IMPERIAL AND EARLY SOVIET RUSSIA - Суворова, Наталья (Porównania, 2019)
In the article, on the basis of records and sources of personal origin, a “Polish element” is revealed in the colonial institutions of late imperial and early Soviet Russia. Taking into account the qualitative characteristics of a wider group – colonization experts, the author attempts to identify various additional factors, in addition to state policy and national preferences proper, the formation of hierarchies of identities in the group. Typologization in combination with the analysis of career biographies of officials of Polish origin allows us to reconstruct individual socio-cultural characteristics of the group, including socio-political sentiments, the level and nature of education, occupational diseases.